(untitled) (Journal of Mechanical Engineering, 2009)
Drag and torque coefficients of a stationary five bladed vane type rotor have been investigated in this present research work by measuring the pressure distribution on the blade surfaces at various rotor angles. The experimental investigation has been performed at Reynolds number 1.65 x 105 in a uniform flow jet produced by an open circuit wind tunnel. It has been observed that the total static torque coefficient increases from 0° to 10°, and reaches its maximum value and then decreases up to 30°. From this point, the total static torque increases up to 72°. Total static torque coefficient at different rotor angles curve repeats from 72° to 144°, 144° to 216°, 216° to 288°, and 288° to 360° angle of rotation. A quasi-steady approach has been applied for the prediction of dynamic performance of the rotor using the static drag and torque coefficients. This method results in a fair agreement with the measured power coefficient. Keywords: Vertical axis wind turbine, vane type rotor, drag coefficient, torque coefficient. doi:10.3329/jme.v39i2.1852 Journal of Mechanical Engineering, Vol. ME39, No. 2, Dec. 2008 95-99